GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, AND SUSTAINABILITY REPORT TO FIRM VALUE - Yuria Mendra; Putu Wenny SAITRI; Ni Putu Sri MARIYATNI (Indonesia Strategic Sustainability, 2021)
Firm value is the company's performance which is reflected by the stock price which is formed by the demand and supply of the capital market which reflects the public's assessment of the company's performance. Several factors that can affect firm value include good corporate governance, corporate social responsibility, and sustainability reports. This study aims to analyze the influence of Good Corporate Governance, Corporate Social Responsibility, and Sustainability Report on Firm Value on the Indonesia Stock Exchange. The research population is manufacturing companies listed on the Indonesia Stock Exchange. The sample in the study of 46 companies was determined based on the purposive sampling method. The results showed that good corporate governance, corporate social responsibility had no effect on firm value while the sustainability report had no effect on firm value. The limitations and suggestions in this study are that this study uses a manufacturing company with an observation period of three years. Further researchers are expected to increase the observation period and increase the number of samples to expand the research results. For further research it is expected to develop and multiply the variations of the independent variables used such as environmental performance, company size